RANCANG BANGUN APLIKASI UJIAN ONLINE STUDI KASUS: SMK 1 PGRI CIKAMPEK - dede firmansyah saefudin; Yuli Komalasari; Evi Maesyari (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2020)
The development of technology in the digital era is now very fast along with the growth of industries from all sectors. The 4.0 industrial revolution has begun to enter its era, which emphasizes the pattern of the digital economy, artificial intelligence, big data, robotic, or known as the phenomenon of disruptive innovation. Education in the era of Industrial Revolution 4.0 or known as Education 4.0 is a phenomenon that responds to the need for the emergence of the industrial revolution 4.0 where humans and machines are aligned to get solutions, solve problems and of course discover new possibilities of innovation. The Era of Education 4.0 is very influential for the world of education, as it also experiences an increase in quality, speed and practicality. Online exams can be said to belong to the era of Education 4.0 because conventional exams (manual) have shifted towards computerization. Online test (Online Test) is one of the methods of evaluating learning outcomes or measuring a person's ability level using a computer. Therefore, the authors researched the web-based online exam system at SMK PGRI Cikampek. Currently the Midterm Examination (UTS) and Graduation Examination (UKK) systems that are implemented at the school are still conventional (manual). So that teachers often experience technical obstacles in processing questions and exam results, such as broken answer sheets, uneven distribution of questions, leakage of questions caused during distribution, and so on. With the online examination system the school can reduce or even minimize the problems that occur in the implementation of conventional exams (manual) because with a computerized system everything can be managed and monitored more neatly easily and centrally.